Peran Guru dalam Meningkatkan Kedisiplinan pada Siswa SDN 28 Bisang - Nayla Nayla (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to determine the teacher's role in increasing the discipline of students at SDN 28 Bisang and to find out the supporting factors and inhibiting factors for the role of teachers in increasing the discipline of students at SDN 28 Bisang. The research was conducted at SDN 28 Bisang. This research approach is a qualitative descriptive with data collection techniques in the form of observation and interviews. The collected data were then analyzed using the techniques proposed by Milles and Huberman, including data reduction, data presentation, and drawing conclusions. The results showed that the teacher's role in increasing the discipline of students at SDN 28 Bisang included: providing an example of discipline for students by coming to school on time; giving advice to students about discipline; reprimand and give punishment to students who arrive late; scold students who often (repeatedly) come late; and control the activities of students at school and at home. Thus, the teacher in this case has more of a role as an educator and role model than just being a teacher. Supporting factors and inhibiting factors for the teacher's role in improving the discipline of students at SDN 28 Bisang, among others, the supporting factors are the application of school rules and regulations, the role of the principal who is quite strict about disciplinary problems for both teachers and students. Whereas the inhibiting factors are the lack of cooperation between fellow teachers, the lack of awareness of students to become disciplined people, the lack of awareness of parents in paying attention to the discipline of students when at home, there are still many teachers who give assignments individually rather than group assignments, and teachers often get criticism and suggestions that are not constructive from the community or parents of students.